Study of AgLiLSX for Single-Stage High-Purity Oxygen Production - Daniel Ferreira (2014)
Commercial adsorbents do not exhibit argon/oxygen equilibrium selectivity above 1. However, in the past decade, Air Products and Chemicals developed an argon/oxygen selective silver-based zeolite, AgLiLSX. In this contribution, the authors studied and characterized the AgLiLSX adsorbent to provide fundamental data to evaluate its potential for high-purity oxygen production in a single-stage PSA unit. Oxygen, nitrogen, and argon adsorption isotherms and breakthroughs curves were obtained, and moderate equilibrium selectivity (alpha(N2/O2) = 4.98 and alpha(Ar/O2) = 1.14 at 1 bar and 25 degrees C), high working capacity (0.45 mol.kg(1) for nitrogen, between 1.4 and 0.2 bar at 25 degrees C), and superior performance were observed. The authors concluded that this adsorbent can allow the production of a 95+% oxygen stream in a single-stage PSA operation.